Modelling of knowledge and conspiracy beliefs on childhood vaccine hesitancy among parents in Kelantan using Malay validated questionnaires - Zin, Nur Dalilah Mohd (2024)
Background: Globally, childhood vaccine hesitancy remains a significant public health concern. Knowledge is well-known influence on the parental’s vaccination decision. Additionally, in light of COVID-19 pandemic, vaccine conspiracies theories worsen the hesitancy. However, local studies looking on this relationship towards vaccine hesitancy using Malay language validated tools were scarce. Objectives: This study aimed, firstly to translate and validate One-dimensional Knowledge scale (OKS), Vaccine Conspiracy Beliefs scale (VCBS) and Modified Vaccine Hesitancy scale (MVHS) into Malay language and secondly, to model relationship of demographic variables, knowledge, and conspiracy belief on childhood vaccine hesitancy among parents in Kelantan using structural equation modelling. Methodology: This was a cross-sectional study conducted in two phases. Phase I, involved translation of the OKS, VCBS and MVHS into Malay version, from April 2023 till June 2023. The scales were translated into Malay based on established guidelines. Content and face validity were assessed involving six expert panels and 10 parents respectively. The data was analysed using Microsoft Excel 365. Then, Phase II was continued between July 2023 till March 2024 involving 270 parents with children aged ≤ 7 years. Confirmatory Factor Analysis (CFA) was used to ensure the scales used were valid and reliable to measure the study variables, then, structural equation modelling (SEM) was performed to determine the relationship between variables. Test-retest reliability was determined to ensure stability of newly translated scales. Data was analysed using IBM SPSS version 26 and Mplus version 8. Results: Phase 1, the M-OKS, M-VCBS and M-MVHS achieved recommended scores of ≥ 0.83 for item indices and scale indices for content and face validity indices. Phase II, the measurement model of M-OKS, consist of unidimensional 10-items demonstrated good model fit (CFI= 0.976, TLI= 0.969, RMSEA (90%CI) = 0.053 (0.030, 0.074), WRMR = 0.877). The 8-item of M-VCBS with correlated items showed good model fit (CFI= 0.977, TLI= 0.967, RMSEA (90% CI) = 0.053 (0.020, 0.082), SRMR = 0.028). The 9-item of M-MVHS consist of two domain “Lack of confidence” and “Risk perception” incorporating correlated items achieved good model fitness (CFI= 0.970, TLI= 0.957, RMSEA (90% CI) = 0.057 (0.031, 0.082), SRMR= 0.031). Composite reliability for M-OKS, M-VCBS and M-MVHS ranged from 0.741 to 0.935 and AVE values of ≥ 0.5, indicating all scales demonstrated good convergent validity. The test-retest reliability, measured by the Intra-class Correlation Coefficient (ICC) ranged from 0.730 to 0.854, indicating good stability for all scales. The final structural model consist of ten hypotheses exhibits good model fit based on the fit indices (CFI= 0.961, TLI= 0.954, RMSEA (90% CI) = 0.040 (0.032, 0.053), SRMR= 0.043). Several indirect relationships were identified between pathways towards vaccine hesitancy. Conclusion: This study provides valid and reliable Malay-language tools to measure knowledge and conspiracy beliefs on childhood vaccine hesitancy among parents in Kelantan. The present study demonstrated the significant relationship of knowledge and conspiracy beliefs on parental vaccination decision, offering valuable insights for public health authorities and policy maker to devise targeted strategies in increasing vaccination uptake.